China's soft power projection across the oceans. (2nd January 2016) - Ghosal Singh, Antara
ABSTRACT: At a time when the focus of most of the academic research on China is on the geopolitical developments in the South China Sea and the panning out of the United States' "next phase of rebalance strategy" in Asia, this paper draws attention to China's charm offensive across the Atlantic. It explores the political undertones of China's soft power push in the developed western world, especially in the context of its evolving relationship with the United States. In the final section, the paper tracks the implication of these developments on India and Indian policymaking.